2015
DOI: 10.1186/s12877-015-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short term elastic resistance training on muscle mass and strength in untrained older adults: a randomized clinical trial

Abstract: BackgroundThe current recommendations on resistance training involving older adults have reported an improvement of body composition variables. Despite this, there is a lack of knowledge on how elastic resistance training (ERT) affects the muscle mass in older adults population. The purpose of this study was to determine the effects of a short-term ERT on muscle mass of health and untrained older adults.MethodsForty older adults were randomized into two groups of 20 individuals each: Control Group (CG = 66.2 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 56 publications
(65 reference statements)
5
34
0
7
Order By: Relevance
“…The men and women accounted for 78.7% and 21.3%, respectively, and the male‐to‐female ratio was 3.69:1. The average body mass index (BMI) was 24.00 ± 3.87 kg/m 2 , and the ages and BMI were similar to those reported previously (Martins et al., ; O'Shea et al., ). The average complication was 1.17 per person, which was less than that in O'Shea's research.…”
Section: Discussionsupporting
confidence: 85%
“…The men and women accounted for 78.7% and 21.3%, respectively, and the male‐to‐female ratio was 3.69:1. The average body mass index (BMI) was 24.00 ± 3.87 kg/m 2 , and the ages and BMI were similar to those reported previously (Martins et al., ; O'Shea et al., ). The average complication was 1.17 per person, which was less than that in O'Shea's research.…”
Section: Discussionsupporting
confidence: 85%
“…The findings of this research support the findings by Colado and Triplett (2008), Martins et al (2015) and Colado et al (2012). For example, Colado and Triplett (2008), reported that FM decreased and FFM increased significantly after 10-week of VRT for twice a week among sedentary women.…”
Section: Variable Resistance Training On Body Compositionsupporting
confidence: 87%
“…If they answered questionnaire questions positively, they were excluded. PAR-Q questionnaire is a tool for screening and evaluating the quality of participation in physical activity (Martins et al, 2015). Subjects also conducted Short Physical Performance Battery Protocol (SPPB) and those who scored a score of less than nine (SPPB≤9) were excluded from the study (Martins et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…PAR-Q questionnaire is a tool for screening and evaluating the quality of participation in physical activity (Martins et al, 2015). Subjects also conducted Short Physical Performance Battery Protocol (SPPB) and those who scored a score of less than nine (SPPB≤9) were excluded from the study (Martins et al, 2015). A sports specialist, with a lifeguard on alert outside the water to watch the subjects, conducted the training course in water.…”
Section: Methodsmentioning
confidence: 99%